EngOps – Ein Leitbild für das agile Zusammenwirken von Engineering und Operations - Anacker, Harald; Dumitrescu, Roman; Michels, Nico; Rasor, Rik (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Um global erfolgreich zu bleiben, wird es bald nicht mehr ausreichen, Kriterien wie ein gutes Produktdesign zu erfüllen. Stattdessen muss der Kundennutzen kontinuierlich über den Produktlebenszyklus hinaus gesteigert werden. Tech-Konzerne verzeichnen bereits Erfolge und verkörpern den Wandel schon heute. Vor diesem Hintergrund ist ein neues Leitbild in der Entwicklung und dem Betrieb von zukünftigen, technischen Systemen erforderlich. EngOps soll diesen Bedarf decken und steht für die agile Kollaboration zwischen Engineering und Operations. Alle Teile des Unternehmens sollen ständig miteinander kooperieren, um so beispielsweise wandelbare Produkte auch nach dem Verkauf entwickeln zu können.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

An In-depth Study of Java Deserialization Remote-Code Execution Exploits and Vulnerabilities - Sayar, Imen; Bartel, Alexandre; Bodden, Eric; Le Traon, Yves (ACM Transactions on Software Engineering and Methodology)
Nowadays, an increasing number of applications uses deserialization. This technique, based on rebuilding the instance of objects from serialized byte streams, can be dangerous since it can open the application to attacks such as remote code execution (RCE) if the data to deserialize is originating from an untrusted source. Deserialization vulnerabilities are so critical that they are in OWASP’s list of top 10 security risks for web applications. This is mainly caused by faults in the development process of applications and by flaws in their dependencies, i.e., flaws in the libraries used by these applications. No previous work has studied deserialization attacks in-depth: How are they performed? How are weaknesses introduced and patched? And for how long are vulnerabilities present in the codebase? To yield a deeper understanding of this important kind of vulnerability, we perform two main analyses: one on attack gadgets, i.e., exploitable pieces of code, present in Java libraries, and one on vulnerabilities present in Java applications. For the first analysis, we conduct an exploratory large-scale study by running 256 515 experiments in which we vary the versions of libraries for each of the 19 publicly available exploits. Such attacks rely on a combination of gadgets present in one or multiple Java libraries. A gadget is a method which is using objects or fields that can be attacker-controlled. Our goal is to precisely identify library versions containing gadgets and to understand how gadgets have been introduced and how they have been patched. We observe that the modification of one innocent-looking detail in a class – such as making it public – can already introduce a gadget. Furthermore, we noticed that among the studied libraries, 37.5% are not patched, leaving gadgets available for future attacks. For the second analysis, we manually analyze 104 deserialization vulnerabilities CVEs to understand how vulnerabilities are introduced and patched in real-life Java applications. Results indicate that the vulnerabilities are not always completely patched or that a workaround solution is proposed. With a workaround solution, applications are still vulnerable since the code itself is unchanged.
Keywords: Software

Fluently specifying taint-flow queries with fluentTQL - Piskachev, Goran; Späth, Johannes; Budde, Ingo; Bodden, Eric (Empirical Software Engineering)

To what extent can we analyze Kotlin programs using existing Java taint analysis tools? - Krishnamurthy, Ranjith; Piskachev, Goran; Bodden, Eric

How far are German companies in improving security through static program analysis tools? - Piskachev, Goran; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven; Bodden, Eric

On the Treatment of Optimization Problems with L1 Penalty Terms via Multiobjective Continuation - Bieker, Katharina; Gebken, Bennet; Peitz, Sebastian (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We present a novel algorithm that allows us to gain detailed insight into the effects of sparsity in linear and nonlinear optimization, which is of great importance in many scientific areas such as image and signal processing, medical imaging, compressed sensing, and machine learning (e.g., for the training of neural networks). Sparsity is an important feature to ensure robustness against noisy data, but also to find models that are interpretable and easy to analyze due to the small number of relevant terms. It is common practice to enforce sparsity by adding the ℓ1-norm as a weighted penalty term. In order to gain a better understanding and to allow for an informed model selection, we directly solve the corresponding multiobjective optimization problem (MOP) that arises when we minimize the main objective and the ℓ1-norm simultaneously. As this MOP is in general non-convex for nonlinear objectives, the weighting method will fail to provide all optimal compromises. To avoid this issue, we present a continuation method which is specifically tailored to MOPs with two objective functions one of which is the ℓ1-norm. Our method can be seen as a generalization of well-known homotopy methods for linear regression problems to the nonlinear case. Several numerical examples - including neural network training - demonstrate our theoretical findings and the additional insight that can be gained by this multiobjective approach.

An update for taxonomy designers: Methodological guidance from information systems research - Kundisch, Dennis; Muntermann, J.; Oberländer, A. M.; Rau, D.; Röglinger, M.; Schoormann, T.; Szopinski, Daniel (Business & Information Systems Engineering)

Durchdrungenheit. Texte und Gespräche. - Eke, Norbert; Zaimoglu , Feridun

Investigation and Improvement of Processing Parameters of a Copper-Filled Polymer Filament in Fused Filament Fabrication as a Basis for the Fabrication of Low-Porosity Metal Parts - Moritzer, Elmar; Elsner, Christian Lennart (Macromolecular Symposia)

Development of a Procedure for the Assessment of Material Potentials under Consideration of the Weld Seam Quality for Multi-Material Applications in the FDM Process - Moritzer, Elmar; Wächter, Julian (Macromolecular Symposia)

Deformationsarme Fügeverbindungen mittels prozessoptimiertem Schneidclinchen - Han, Daxin
Lightweight materials such as aluminium and ultra-high-strength steel are increasingly being used in modern material mixed design in car body construction. As a fixing method for hybrid joining with structural adhesive, clinching has the advantage over other mechanical joining technologies that different materials can be joined without an auxiliary joining part and pre-hole. Due to the large degree of deformation in the joining partners, strong in-plane and out-of-plane material flows occur during the setting process, which can lead to plastic deformation. The aim of this work is the further development of shear-clinching for low-deformation of aluminium-steel joints. To gain a basic understanding of the joint deformation, the deformation of the joint partners during the setting process is identified step by step. Based on the knowledge gained, the deformation-related influencing factors are investigated experimentally. Thus, optimisation approaches as well as suggested handling methods for the production of a low-deformation shear-clinching joint are derived. For the realisation of the common narrow flange, which is to be characterised as deformation-sensitive due to a small edge distance, a numerically supported tool modification is carried out and subsequently experimentally validated.

Differentiation of an SBFE model in the context of material parameter determination - Itner, Dominik; Gravenkamp, Hauke; Dreiling, Dmitrij; Birk, Carolin; Henning, Bernd

Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000, (= Drama zwischen Text und Bühne 1)

Judgment or Choice? An Experimental Comparison of Evaluation Approaches for External Crowdvoting - Laux, Florian; Kundisch, Dennis

PTBP2 – a gene with relevance for both Anorexia nervosa and body weight regulation - Zheng, Yiran; Rajcsanyi, Luisa Sophie; Herpertz-Dahlmann, Beate; Seitz, Jochen; de Zwaan, Martina; Herzog, Wolfgang; Ehrlich, Stefan; Zipfel, Stephan; Giel, Katrin; Egberts, Karin; Burghardt, Roland; Föcker, Manuel; et al. (Translational Psychiatry)
Abstract Genetic factors are relevant for both eating disorders and body weight regulation. A recent genome-wide association study (GWAS) for anorexia nervosa (AN) detected eight genome-wide significant chromosomal loci. One of these loci, rs10747478, was also genome-wide and significantly associated with body mass index (BMI). The nearest coding gene is the Polypyrimidine Tract Binding Protein 2 gene ( PTBP2 ). To detect mutations in PTBP2 , Sanger sequencing of the coding region was performed in 192 female patients with AN (acute or recovered) and 191 children or adolescents with (extreme) obesity. Twenty-five variants were identified. Twenty-three of these were predicted to be pathogenic or functionally relevant in at least one in silico tool. Two novel synonymous variants (p.Ala77Ala and p.Asp195Asp), one intronic SNP (rs188987764), and the intronic deletion (rs561340981) located in the highly conserved region of PTBP2 may have functional consequences. Ten of 20 genes interacting with PTBP2 were studied for their impact on body weight regulation based on either previous functional studies or GWAS hits for body weight or BMI. In a GWAS for BMI (Pulit et al. 2018), the number of genome-wide significant associations at the PTBP2 locus was different between males (60 variants) and females (two variants, one of these also significant in males). More than 65% of these 61 variants showed differences in the effect size pertaining to BMI between sexes (absolute value of Z -score >2, two-sided p < 0.05). One LD block overlapping 5′UTR and all coding regions of PTBP2 comprises 56 significant variants in males. The analysis based on sex-stratified BMI GWAS summary statistics implies that PTBP2 may have a more pronounced effect on body weight regulation in males than in females.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Abstract Purpose The COVID-19 pandemic and public measures have a direct impact on the nutrition situation; studies show changes in food consumption, eating behavior or body weight but complex pattern analyses of changes rarely exist. Methods During the first German lockdown, a web-based survey was conducted among adults. It included 33 questions about changes in food intake, eating habits and physical activity, as well as anthropometrics and sociodemographic factors. Patterns of change were calculated based on changes in food intake and eating habits using two-step cluster analysis. To identify influencing factors for assignment to the patterns of change, binary logistic regression analyses were performed. Results Data from 2103 participants (81% female, 40 ± 14 years) were considered for analysis. Increased stockpiling, cooking, and variation in preparation was reported by 50–70%. The constant pattern (C-P, 36%) reported little change besides the above. The health-oriented pattern (HO-P; 37%) reported eating more healthy foods, avoiding unhealthy foods, and eating less and less frequently. The emotional-driven pattern (ED-P; 28%) exhibits higher influence of emotions on eating behavior, less avoidance of unhealthy foods, and increased consumption of sweets, pastries, and alcohol. The odds of changing eating behavior either to HO-P or ED-P were higher in women, people with migration background, younger participants, and increased with BMI categories. Conclusion Both, the ED-P and HO-P, exhibit distinctive reactions in eating habits and food intake when dealing with a distressing experience. In subgroups, these may lead to disturbances in eating behavior and increase the risk for eating disorders and obesity.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Prospective association of family members’ sugar-sweetened beverages intake with children’s sugar-sweetened beverages consumption in China - Liu, Xue-Ting; Xiong, Jing-Yuan; Xu, Yu-Jie; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose We aimed to investigate whether parental and siblings’ sugar-sweetened beverage (SSB) intake had prospective impact on children’s SSB consumption, and the potential sex difference in these associations. Methods This study included a total of 904 children and their parents enrolled from 2004 to 2011 China Health and Nutrition Survey (CHNS) cohort study. SSB consumption information was estimated using a short dietary questionnaire and total energy intake was assessed with three-day 24-h dietary assessments at recruitment and follow-up surveys. Multivariate logistic or linear regression analyses were used to assess the association for SSB consumption between parents, siblings and children after adjusting for age, body mass index (BMI) z -score, household income and parental educational level. Results In this study, a majority (87.6%) of children consumed SSB. Among them, the median consumption of SSB was 70.3 ml/day per capita and 205.4 ml/day per consumer. Parental SSB consumption was relevant to children’s SSB consumption, and this association was more pronounced in boys than in girls. Meanwhile, fathers seemed to have a stronger impact on whether children consume SSB than mothers which was reflected by lower P and higher OR. Additionally, children’s SSB intake was prospectively associated with their older siblings’ SSB consumption ( P for trend < 0.03). Conclusions Parental and older siblings’ SSB consumption was relevant to children’s SSB intake. Particularly, boys were more susceptible to parental impact than girls, and fathers seemed to have a greater influence on children than mothers.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Towards new nutritional policies for brain health: A research perspective on future actions - Adan, Roger A.H.; Cirulli, Francesca; Dye, Louise; Higgs, Suzanne; Aarts, Kristien; van der Beek, Eline M.; Buitelaar, Jan K.; Destrebecq, Frédéric; De Witte, Elke; Hartmann, Tobias; Korosi, Aniko; Libuda, Lars; et al. (Brain, Behavior, and Immunity)
Keywords: Behavioral Neuroscience; Endocrine and Autonomic Systems; Immunology

Low leptin levels are associated with elevated physical activity among lean school children in rural Tanzania - Ludwig, Christine; Knoll-Pientka, Nadja; Mwanri, Akwilina; Erfle, Celina; Onywera, Vincent; Tremblay, Mark S.; Bühlmeier, Judith; Luzak, Agnes; Ferland, Maike; Schulz, Holger; Libuda, Lars; Hebebrand, Johannes (BMC Public Health)
Abstract Background In Sub-Saharan African countries, rapid urbanization and increasing socio-economic status are associated with a transition to decreased physical activity (PA). A more sedentary lifestyle is linked to increased body fat leading to increments in leptin levels. Since rodent and human studies in high-income countries have shown that starvation-induced hypoleptinemia triggers high PA, efforts are warranted to pursue the hypothesis that low leptin levels in lean children of low- and middle-income countries (LMIC) are also associated with high PA. Methods In this cross-sectional study, we assessed seven-day PA with triaxial accelerometry (ActiGraph GT3X) among 223 primary school children (9 to 12 years of age) in rural Tanzania. Moderate-to-vigorous PA (MVPA) and total accelerometer counts per day were outcome variables. Leptin was determined using enzyme linked immunosorbent assay tests from dried blood spots. Anthropometric assessments were conducted and food insecurity and socio-demographic data were gathered using semi-structured interviews. Results In this sample of school children in rural Tanzania, leptin concentrations (median: 0.91 ng/mL, P25: 0.55, P75: 1.69), body mass index z-scores (median: -1.35, P25: -1.93, P75: -0.82), and height-for-age-z-scores (median: -1.16, P25: -1.96, P75: -0.61) were low. In contrast, PA levels were high with a median MVPA time of 119 min/day. Linear regression confirmed that leptin levels were negatively associated with MVPA (beta: -18.1; 95%CI: -29.7; -6.5; p = 0.002) and total accelerometer counts (beta: -90,256; 95%CI: -154,146; -26,365; p = 0.006). Children residing in areas with better infrastructure had lower MVPA levels ( p < 0.001) and tended to have higher leptin levels ( p = 0.062) than children residing in areas only reachable via dirt roads. Conclusion Our cross-sectional field study is the first that supports the hypothesis of low leptin levels as a potential endocrine trigger of high PA in lean children of a LMIC. We observed early signs of a PA transition towards a less active lifestyle in a subgroup residing in areas with better infrastructure that concomitantly tended to have higher leptin concentrations. Considering that area-dependent PA differences were more pronounced among girls than boys, whereas differences in leptin levels were less pronounced, not only biological, but also external factors explain PA transition.
Keywords: Public Health; Environmental and Occupational Health